Magnetoelectric vibrational energy harvester utilizing a phase transitional approach. (28th November 2018) - Staruch, Margo; Yoo, Jin-Hyeong; Jones, Nicholas; Finkel, Peter
Abstract: Abstract : A broadband magnetoelectric energy harvester, consisting of Fe1− x Ga x (Galfenol) as the magnetostrictor and a relaxor ferroelectric single crystal as the piezoelectric, has been designed and optimized. Finite element analysis (FEA) has been employed to show that either a linear displacement or a 180° rotation of a magnet is sufficient to achieve maximum stroke from the Galfenol rod, which induces a rhombohedral to orthorhombic phase transition in Pb(In1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 that produces a large jump in voltage. A rotational design based on a pendulum with an unbalanced mass was fabricated and used to confirm the validity of our FEA model.